Scada-net mạng thông tin dữ liệu thời gian thực - Lợi, Phí Mạnh (Journal of Computer Science and Cybernetics, 2016)
This article presents the real time data network SCADA-NET as a Information System for Operating and Management of National Power System and it’s Design bases on LNET Software package. SCADA-NET operates on 500 kV fiber optic.